2022
DOI: 10.1101/2022.03.01.482462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid hypermutation B cell trajectory recruits previously primed B cells upon third SARS-CoV-2 mRNA vaccination

Abstract: High antibody affinity against the ancestral SARS-CoV-2 strain seems to be necessary (but not always sufficient) for the control of emerging immune-escape variants. Therefore, aiming at strong B cell somatic hypermutation - not only at high antibody titers - is a priority when utilizing vaccines that are not targeted at individual variants. Here, we developed a next-generation sequencing based SARS-CoV-2 B cell tracking protocol to rapidly determine the level of immunoglobulin somatic hypermutation at distinct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…The results showed that the NAbs induced by heterologous mRNA and viral vector as a third dose vaccination had broad neutralizing activity against several subvariants of SARS-CoV-2. Consistent with a previous study, after the homologous mRNA booster, the percentage of somatic hypermutated memory B cells increased and indicated B cell affinity maturation (Paschold et al, 2022). In comparison, the median %inhibition of neutralizing activity against Omicron BA.2 and BA.4/5 showed a significantly lower susceptibility than against wild type.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the NAbs induced by heterologous mRNA and viral vector as a third dose vaccination had broad neutralizing activity against several subvariants of SARS-CoV-2. Consistent with a previous study, after the homologous mRNA booster, the percentage of somatic hypermutated memory B cells increased and indicated B cell affinity maturation (Paschold et al, 2022). In comparison, the median %inhibition of neutralizing activity against Omicron BA.2 and BA.4/5 showed a significantly lower susceptibility than against wild type.…”
Section: Discussionsupporting
confidence: 91%
“…This difference persisted as a strong trend at the memory time point. These results are consistent with the fact that germinal centers remain active for several weeks after vaccination (Turner et al, 2021), with continuous evolution of the B cell compartment for several months (Cho et al, 2021) and accumulation of somatic hypermutations (Kim et al, 2022;Paschold et al, 2022;Turner et al, 2021). Hence, an early second dose likely corresponds to a suboptimal timing in terms of re-exposure to the cognate antigen, while a longer interval allows for a better evolution of the B cell repertoire.…”
Section: Discussionsupporting
confidence: 81%
“…Herein, we observed that the heterologous mRNA-based booster, but not the AZD1222-boosted, effectively produced a high level of cross-neutralization against SARS-CoV-2 variants 28 days after the booster dose. The breadth and cross-reactivity of NAbs after the third dose may be related to increasing memory B cell affinity maturation through extensive somatic hypermutation like those observed in a previous mRNA-boosted study (Paschold et al, 2022). However, reductions in neutralizing activity against Omicron variants were found compared with those against Delta variants in both BNT162b2-primed and CoronaVac-primed individuals (Assawakosri et al, 2022, Pérez-Then et al, 2022, Planas et al, 2022.…”
Section: Discussionmentioning
confidence: 68%